Анализ генетического потенциала племенных быков Брянской области по гену BoLA-DRB3 - Смазнова, И.А.; Немцова, К.Н.; Заякин, В.В.; Нам, И.Я. (Фактори експериментальної еволюції організмів, 2013)
Aim. Analisis of gene BOLA-DRB3 polymorphism of breeding bulls. Methods. We used the method of PCR-RFLP. Results. Spectrum of resistance and susceptibility alleles has beende terminated. Conclusions. Results obtained will be used to composite cattle leucosis resistance herd.